PENGARUH INFLASI, NILAI KURS DAN SUKU BUNGA TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - sopi, sopi - (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
Stock return is the return obtained from investment. Investors' expectations in investing in stocks other than being the owner of a company with a certain proportional ownership, the shares invested are expected to be able to provide a certain rate of return. The purpose of this study was to determine the effect of inflation, exchange rates and interest rates on stock returns in banking companies listed on the Indonesia Stock Exchange for the period 2017-2019. The population in this study were all banking companies listed on the Indonesia Stock Exchange for the 2017-2019 period, totaling 45 companies. The sampling technique used purposive sampling method, in order to obtain a sample of 27 company samples. The data collection method used in this study is secondary data with documentation techniques by collecting existing online documents in the form of financial reports obtained from www.idx.co.id. With the number of observations for 3 consecutive years. The data analysis technique used is multiple linear regression using the SPSS version 16 program. The results of this study indicate that the independent variable inflation, exchange rates and interest rates have an effect on stock returns with a significance value of 0.000 <0.05. The results of the study that partially Inflation has an effect on Stock Returns indicated by a significance value of 0.000 <0.05. Exchange rate has an effect on Stock Return indicated by a significance value of 0.000 <0.05. Interest rates have an effect on Stock Returns indicated by a significance value of 0.000 <0.05. The conclusion from the results of this study is that inflation, exchange rates and interest rates affect Stock Returns in banking companies listed on the Indonesia Stock Exchange for the period 2017-2019. Suggestions that can be conveyed to investors who are going to invest are advised to pay more attention to these variables in making investment decisions so as to reduce investment risks such as decreased stock returns